Pengarsipan Web (Web Archiving) Terhadap Web Terkait Pandemi COVID-19 di Indonesia - Nuraini Ahmad (Jurnal Gema Pustakawan, 2022)
The web is a medium of communication and information that is widely used by Indonesian people today, but it has the inherent property of being easily lost. For this reason, the web that stores information and records the activities of the Indonesian people needs to be preserved because it can be considered as a document of historical and cultural heritage value. Preserving the web in an archive format so that it remains accessible in the future is called web archiving. The COVID-19 pandemic that hit Indonesia is considered an extraordinary event. Thus, information about the COVID-19 pandemic, which is widely disseminated via the web, is seen as important to be preserved through web archiving, so that future generations can still access it. The problem is, in Indonesia web archiving in the national scope is no longer active, even though it was once organized by the National Library of Indonesia in 2010-2015. In addition, the field of web archiving has not been widely researched by Indonesian academics. This prompted the author to conduct this research which aims to initiate web archiving steps for webs related to the COVID-19 pandemic in Indonesia. The research method used to perform web archiving is the web archiving life cycle model (WALCM) method developed by the Archive-It team. The WALCM method can be applied to web archiving related to the COVID-19 pandemic in Indonesia. The conclusion of this study is that a number of websites have been successfully archived according to policy. However, the number is not significant due to limited resources.